Tricyclic antipsychotics and antidepressants can inhibit α5‐containing GABAA receptors by two distinct mechanisms. (7th March 2022) - Bampali, Konstantina; Koniuszewski, Filip; Silva, Luca L.; Rehman, Sabah; Vogel, Florian D.; Seidel, Thomas; Scholze, Petra; Zirpel, Florian; Garon, Arthur; Langer, Thierry; Willeit, Matthäus; Ernst, Margot
Abstract : Background and Purpose: Many psychotherapeutic drugs, including clozapine, display polypharmacology and act on GABAA receptors. Patients with schizophrenia show alterations in function, structure and molecular composition of the hippocampus, and a recent study demonstrated aberrant levels of hippocampal α5 subunit‐containing GABAA receptors. The purpose of this study is to investigate the effects of tricyclic compounds on α5 subunit‐containing receptor subtypes. Experimental Approach: Functional studies of effects by seven antipsychotic and antidepressant medications were performed in several GABAA receptor subtypes by two‐electrode voltage‐clamp electrophysiology using Xenopus laevis oocytes. Computational structural analysis was employed to design mutated constructs of the α5 subunit, probing a novel binding site. Radioligand displacement data complemented the functional and mutational findings. Key Results: The antipsychotic drugs clozapine and chlorpromazine exerted functional inhibition on multiple GABAA receptor subtypes, including those containing α5‐subunits. Based on a chlorpromazine binding site observed in a GABA‐gated bacterial homologue, we identified a novel site in α5 GABAA receptor subunits and demonstrate differential usage of this and the orthosteric sites by these ligands. Conclusion and Implications: Despite high molecular and functional similarities among the tested ligands, they reduce GABA currents by differential usage of allosteric and orthosteric sites. The chlorpromazine site we describe here is a new potential target for optimizing antipsychotic medications with beneficial polypharmacology. Further studies in defined subtypes are needed to substantiate mechanistic links between the therapeutic effects of clozapine and its action on certain GABAA receptor subtypes.